Aggregation‐Induced Emission of Highly Planar Enaminone Derivatives: Unexpected Fluorescence Enhancement by Bromine Substitution. Issue 8 (15th February 2019) - Li, Hua; Shu, Haiyang; Liu, Yang; Wu, Xiaofu; Tian, Hongkun; Tong, Hui; Wang, Lixiang
Abstract: Unlike typical aggregation‐induced‐emission (AIE) molecules with twist/rotor structures, two AIE‐active enaminone derivatives with highly planar conformations are herein reported. Interestingly, the bromine‐substituted enaminone fluorophore (BrE) exhibits unexpected stronger emission in solid states than unsubstituted enaminone fluorophore (HE), which is seldom observed for organic fluorophores. Remarkably, the fluorescence quantum efficiency of BrE crystal is ten times as large as that of HE crystal. Based on single‐crystal analysis and theoretical calculation, the unusual fluorescence behavior is attributed to the important effect of bromide substituents which not only form intermolecular Br⋅⋅⋅Br halogen bonding to block nonradiative relaxation pathways efficiently but also promote the radiative process. Abstract : For two planar enaminone derivatives with aggregation‐induced emission characteristic, the compounds containing intermolecular Br…Br halogen bonding display unexpectedly stronger fluorescence than its analog without bromide substituent in solid states.